Multidimensional Poverty Index in Sarawak - Ian Gerard, Umpang; Rossazana, Ab Rahim (HRMAS, 2025)
This study examines multidimensional poverty in Sarawak using the Multidimensional Poverty Index (MPI) framework, which captures deprivations in health, education, and living standards beyond traditional income-based measures. Drawing on primary survey data from 386 respondents, the Alkire-Foster dual cut-off methodology was applied to identify the extent and intensity of poverty across households. The findings indicate that 90 percent of respondents were classified as non-poor, while 4.4 percent were near poor, 2.6 percent poor, and 2.1 percent severely poor. Deprivations were most pronounced in housing quality, access to healthcare, and nutrition, whereas indicators such as school enrolment and sanitation reflected near-universal access. These results suggest that while Sarawak has made substantial progress in reducing poverty, structural vulnerabilities persist among specific groups. The study underscores the importance of adopting a multidimensional perspective in poverty alleviation policies and highlights the need for targeted interventions to address overlapping deprivations, thereby supporting Malaysia’s broader aspirations under the Shared Prosperity Vision 2030 and the Sustainable Development Goals.